Anatomical site distribution and genotypes of Chlamydia trachomatis infecting asymptomatic men who have sex with men in northeast Thailand. (August 2018) - Hinkan, Saowarop; Chuerduangphui, Jureeporn; Ekalaksananan, Tipaya; Budkaew, Jiratha; Proyrungroj, Kanisara; Pimson, Charinya; Chumworathayi, Bandit; Hanond, Tanyaporn; Pientong, Chamsai
Chlamydia trachomatis is a common agent of sexually transmitted infection, especially in asymptomatic extra-genital sites among men who have sex with men (MSM). This study aims to investigate anatomical site distribution and genotypes of C. trachomatis from asymptomatic MSM in northeast Thailand. Specimens were collected using swabs from anorectal, oropharyngeal, and urethral sites in 346 asymptomatic MSM. C. trachomatis infection was determined by real-time polymerase chain reaction and genotyping was based on sequences of the ompA gene. The results showed that infection by C. trachomatis was most common at the urethral site (29.1%, 101/346) followed by oropharyngeal (17.6%, 61/346) and anorectal site (17.0%, 59/346). In addition, C. trachomatis infection was significantly associated with absence of condom use (odds ratio = 1.909, 95%CI = 1.054–3.457, P  = 0.033) at the urethral site. Overall 49.4% (171/346) of individuals were infected in at least one site. Infection at only the anorectum, oropharynx, or urethra was seen in 9.0, 9.3, and 18.5% of participants, respectively. Concurrent infections at anorectum/oropharynx, anorectum/urethra, oropharynx/urethra, and all three sites were 2.0, 4.3, 4.6, and 1.7%, respectively. Genotype D predominated at the anorectal and urethral sites among asymptomatic MSM in northeast Thailand. Concurrent infection in two or three anatomical sites occurred. C. trachomatis screening at all three sites in asymptomatic MSM is important and should be considered for proper treatment and prevention of transmission.